Pengaruh Pengungkapan Laporan Keberlanjutan, Kinerja Keuangan, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Muhammad Rakan Firdaus; Hexana Sri Lastanti (Ikatan Da'i Indonesia, 2025)
This study aims to examine the effect of sustainability report disclosure, financial performance (measured by profitability and liquidity), and company size on firm value. This research uses secondary data obtained from annual reports and sustainability reports of financial and banking sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The sampling method used in this study is purposive sampling, with a total of 25 companies observed over a period of three years, resulting in 75 firm-year observations. The data analysis was conducted using a quantitative approach with EViews 12 software and panel data regression analysis. The results show that financial performance measured by profitability has a positive and significant effect on firm value. Company size has a negative and significant effect on firm value. Meanwhile, sustainability report disclosure and financial performance measured by liquidity do not have a significant effect on firm value.